2012
DOI: 10.1016/j.ssci.2009.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Results and lessons learned from the ESReDA’s Accident Investigation Working Group

Abstract: Encore récemment, de nombreuses catastrophes industrielles ont frappé les opinions publiques, les instances politiques et les industriels. Beaucoup se sont interrogés sur les causes possibles de tels événements et sur les moyens de les prévenir. L'enquête après accident ou post-événement est l'approche courante pour identifier les faits, leurs causes directes et leurs causes profondes, ainsi que pour définir et mettre en oeuvre des mesures correctives permettant de prévenir des événements similaires dans le fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…This approach contrasts with individual blame logic, where guilty individuals are identified. Choularton (2001), Dechy, Dien, Funnemark, Roed-Larsen, Stoop, and Valvisto (2012), Fahlbruch and Schöbel (2011) and Jacobsson et al (2009) state that the determination of organizational factors or underlying causes is the most important part of learning. Addressing the indirect causes or conditions, independent of the people who are operating, creates a safer environment in which more than just one event will be prevented (Catino, 2008;Jacobsson et al, 2009).…”
Section: Identifying Incident Causesmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach contrasts with individual blame logic, where guilty individuals are identified. Choularton (2001), Dechy, Dien, Funnemark, Roed-Larsen, Stoop, and Valvisto (2012), Fahlbruch and Schöbel (2011) and Jacobsson et al (2009) state that the determination of organizational factors or underlying causes is the most important part of learning. Addressing the indirect causes or conditions, independent of the people who are operating, creates a safer environment in which more than just one event will be prevented (Catino, 2008;Jacobsson et al, 2009).…”
Section: Identifying Incident Causesmentioning
confidence: 99%
“…Recent literature on accident investigation and analysis for instance emphasizes the performance of analysis and the role of the investigators (Hovden et al, 2011;Dechy et al, 2012;Kontogiannis et al, 2000). Hovden et al (2011) described the results of a workshop on multilevel learning, in which it was concluded that the expertise of investigators and their independence are considered the most important conditions for learning.…”
Section: People Involvedmentioning
confidence: 99%
“…This case indicates that care should be taken not to misapply this principle to accident investigation and learning, delegating such obligations to the parties directly affected. We argue, as do Dien et al (2012) and Dechy et al (2012), that investigations should be independent. We furthermore argue, as do Fauchart (2006), that it appears critical to provide some sort of institutional support to facilitate learning.…”
Section: Resultsmentioning
confidence: 73%
“…There are numerous obstacles for establishing successful system of incident reporting which maximizes safety improvements (e.g., [2]). Across different industries there is valuable experience and knowledge related to the accident investigation which improves OEF, [3].…”
Section: Challenges For Better Operational Experiencementioning
confidence: 99%